Ecobrick sebagai Bentuk Aksi Nyata dalam Menjaga Ekosistem Darat Berkelanjutan di Nagari Dilam - Rizka Aghnia; Gustina Erlianti; Amellya Fitri; Rehan Habibi; Muhammad Rofiqi Ikbal; Zahda Yurenda Putri (STKIP Subang, 2025)
Plastic waste has become a critical issue threatening the sustainability of terrestrial ecosystems, including in Nagari Dilam. The lack of public awareness regarding environmentally friendly waste management highlights the need for community service programs that are both practical and solution-oriented. Through the Community Service Program (Kuliah Kerja Nyata or KKN), this activity was carried out using a Participatory Action Research (PAR) approach with the 5T stages: To Know, To Understand, To Plan, To Action, and To Reflection. The results showed an increase in residents’ knowledge and skills in managing plastic waste through the creation of ecobricks. A tangible output of this activity is the construction of a landmark spelling out